DOI: 10.11606/d.102.2014.tde-19012015-104005
|View full text |Cite
|
Sign up to set email alerts
|

Ferrovia, trabalho e habitação: Vilas Operárias de Campinas (1883-1919)

Abstract: Social habitations has faced profound changes with industrialization during the second half of the nineteenth and early twentieth century. The dissemination of new concepts such as comfort and functionality, as well as standards of morality, coupled with the adoption of new technologies and concerns about health issues, led to the transformation of old patterns urban and architectural. Consequently, new types and models of habitations were developed and built for workers of industrial clusters and rail housing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Although the railway managers proposed changes in relation to the use of slave labor, they are not exempt from blame, as it is observed that the use of free labor did not represent a thought with humanitarian intentions, but rather a clash of powers in the face of the time of scarcity of enslaved labor, in order to ensure that work on crops was not interrupted and/or impaired. Guazzelli (2014) complements this information by saying that the workforce used in the Campinas railway was mostly composed of national workers, coming from the state of Minas Gerais, and European immigrants, who came to Brazil from 1885 in order to abandon their former work in agriculture. Thus, "[…] the railroad introduced a regular work dynamics that had not existed until then, directly influencing the formation of work habits within the existing forms of hiring free labor, which until then was mainly employed seasonally" (Guazzelli, 2014, p. 33, our translation), promoting important changes in the hiring of labor and boosting the state's economy.…”
Section: Fôlego: Violence Black Body and The Traces Of Campinas' Slaverymentioning
confidence: 89%
See 1 more Smart Citation
“…Although the railway managers proposed changes in relation to the use of slave labor, they are not exempt from blame, as it is observed that the use of free labor did not represent a thought with humanitarian intentions, but rather a clash of powers in the face of the time of scarcity of enslaved labor, in order to ensure that work on crops was not interrupted and/or impaired. Guazzelli (2014) complements this information by saying that the workforce used in the Campinas railway was mostly composed of national workers, coming from the state of Minas Gerais, and European immigrants, who came to Brazil from 1885 in order to abandon their former work in agriculture. Thus, "[…] the railroad introduced a regular work dynamics that had not existed until then, directly influencing the formation of work habits within the existing forms of hiring free labor, which until then was mainly employed seasonally" (Guazzelli, 2014, p. 33, our translation), promoting important changes in the hiring of labor and boosting the state's economy.…”
Section: Fôlego: Violence Black Body and The Traces Of Campinas' Slaverymentioning
confidence: 89%
“…According to Guazzelli (2014), it is from 1850 onwards that coffee production in the West region of the state of São Paulo develops as a powerful and profitable economic complex. As a result, Campinas is elevated to the category of city in 1842 and becomes a dynamic hub for the Brazilian economy, and much of this growth is due to the creation of the railway system that enabled such development, in addition to housing the history of the use of slave labor in the city.…”
Section: Fôlego: Violence Black Body and The Traces Of Campinas' Slaverymentioning
confidence: 99%
“…Observando a dimensão continental do território brasileiro e a pluralidade cultural e socioeconômica da população, estudar tais agrupamentos habitacionais e os seus aspectos arquitetônicos e urbanísticos se torna uma atividade complexa. Diante desse contexto, valem ser registradas as contribuições de Almeida (2007Almeida ( /2012, Blay (1985), Borba (1994), Chalhoub (1996), Correia (1998), Guazzelli (2014), Gunn e Correia (2005), Heredia (2003), Janke (1999Janke ( /2009, Jeronymo (2012), Miranda (2013), Moreira (2002), Paulitsch (2003), Rago (1985), Sampaio (2002), Timm (2015), Varon (1998), Vianna (2006Vianna ( /2012) e muitos outros, que possuem relevância, principalmente, no que diz respeito ao resgate da história da moradia operária e sua importância na formação de muitas cidades em nosso país. Em linhas gerais, os mencionados autores concentram suas análises em cidades de grande porte, destacando o vocabulário arquitetônico de referência e/ou o processo de monte e desmonte das fábricas e conjuntos residenciais, ficando as cidades de médio porte -a exemplo de Passo Fundo, localizada ao noroeste sul-rio-grandense -, e as análises de projeto arquitetônico e urbanístico em segundo plano.…”
unclassified
“…Segundo Kühl (2008), o patrimônio industrial engloba todos os vestígios da cultura industrial, incluindo os espaços diretamente relacionados com a produção, como oficinas, fábricas, minas e armazéns e outros serviços relacionados, como meios de transporte e estações, habitação operária, locais de culto e educação (Kühl, 2008, p. 51). Assim, os trabalhos de Bárbara Gonçalves Guazzelli (2014) e Gabriela Campagnol (2008) que tratam sobre as vilas operárias, respectivamente, na cidade de Campinas e em usinas de açúcar; a pesquisa de Eduardo Romero Brito (2019) sobre o patrimônio ferroviário; e o de Ana Lara Barbosa Lessa (2015) sobre a preservação das Indústrias Matarazzo em São Paulo demonstram a diversidade de abordagens e temas que podem ter as pesquisas sobre patrimônio industrial.…”
Section: In Tro Du çãOunclassified